A new method to determine varying adsorbed density based on Gibbs isotherm of supercritical gas adsorption - Hailiang Cai; Peichao Li; Zhixin Ge; Yuxi Xian; Detang Lu (Adsorption Science & Technology)
In the calculation of the absolute adsorption of supercritical gas adsorbed on the microporous materials, most existing methods regard the adsorbed density as a constant, which is very unreasonable. In this study, an extended pressure point method combined with Langmuir adsorption model is proposed in which the varying adsorbed density under different pressures is considered at the same time. The utility of the proposed method to correlate accurately the experimental data for supercritical gas adsorption system is demonstrated by high-pressure methane adsorption measurements on two groups of shale samples. Taking advantage of the proposed method, we can obtain the adsorbed density and the adsorbed volume corresponding to different pressures. Compared with the conventional methods under the assumption of fixed and parameterized adsorbed density, the proposed method yields better fitting results with the experimental data. Our work should provide important fundamental understandings and insights into the supercritical gas adsorption system.